ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN: SEBUAH STUDI LITERATUR - Sari, Maxsrita Tassa; Wuryantari, Herlinda P; Putri, Fitria S; Dewi, Poppy Ratna; Pertiwi, Alifatul (AMMER : JOURNAL OF ACADEMIC & MULTIDICIPLINE RESEARCH; Vol 2 No 03 (2023): EDISI OKTOBER - JANUARIDO - 10.32503/ammer.v2i03.3410, 2023)
In every field of business, strategy is important because it is a series of decisions and actions directed at achieving company goals. More than that, entrepreneurs need a marketing strategy for their business. This is very important because it is a fundamental tool planned to achieve company goals. The purpose of this study is to analyze the right marketing strategy in increasing sales. The method used in this research is Systematic Literature Review. The result of this study is that the success of increasing sales of a company depends on its marketing strategy which is based on an analysis of strengths, weaknesses, opportunities, and threats. Strengths and opportunities are the biggest factors in the success of increasing sales of a business